TATA Box Insertion Provides a Selection Mechanism Underpinning Adaptations to Fe Deficiency. Issue 1 (23rd November 2016) - Zhang, Meiling; Lv, Yuanda; Wang, Yi; Rose, Jocelyn K. C.; Shen, Fei; Han, Zhenyun; Zhang, Xinzhong; Xu, Xuefeng; Wu, Ting; Han, Zhenhai
Abstract : TATA-box insertion in the upstream untranslated sequences of genes enhances adaptation to selective pressure. Abstract: Intraspecific genetic variation is essential for the responses and adaption of plants to evolutionary challenges, such as changing environmental conditions. The development of the Earth's aerobic atmosphere has increased the demand for iron (Fe) in organisms, and Fe deficiency has become a limiting environmental factor for plant growth. Here, we demonstrate that genus Malus adapt to Fe deficiency through modification of the Iron-Regulated Transporter1 ( IRT1 ) promoter. Specifically, an IRT1 mutant allele with a TATA-box insertion in the promoter region upstream of the coding region exhibited increased IRT1 expression. The altered IRT1 promoter is responsible for enhancing Fe uptake. Increasing the number of synthetic repeat TATA-boxes correlates with increased promoter activity. Furthermore, we demonstrate that the insertion of the TATA-box correlates with an increase in transcriptional activation via specific binding of the transcription factor IID (MDP0000939369). Taken together, these results indicate that an allelic insertion of a TATA-box in a gene promoter has allowed apple to adapt to the selective pressure posed by Fe deficiency. More broadly, this study reveals a new mechanism for enhancing gene expression to help plants adapt to different environments, providing new insights into molecular genetic divergence in plants.